Peranan Abang Yusuf Puteh dalam pembangunan masyarakat Melayu Sarawak, 1970-2009 / Awg Kasmurie Awg Kitot - Awg Kasmurie, Awg Kitot (2017)
This research set forth the role of Abang Yusuf Puteh in the development of the Sarawak Malay Society from 1970 to 2009. The detailed research opened the role played by Abang Yusuf Puteh towards the development of Sarawak Malay society in the aspects of politics (leadership), economy (poverty) and social (education issues and religious practice). Abang Yusuf Puteh regarded the four aspects as issues that delayed the development of Sarawak Malay society especially the Malay society at the coastal area. The scope of the research begin from 1970, i.e. when Abang Yusuf Puteh was appointed as the first Malay choosen to hold a post as the Secretary of the Sarawak State Government and ended in 2009 when he passed away at the age of 74. During his service, he witnessed the slowdown in the development of the coastal Malay society. Qualitative approach was used for this history research. The discussion in every chapter used the thematic method. Library research was done to examine and analyse the primary source such as official documents, personal papers, speeches, government publications, interview transcriptions and other works. Besides the primary source, secondary source such as book, thesis, dissertation, graduation exercises, journals, conference proceedings, newspapers and magazines were also used as references to solidify the research. The research method was solidified with in-depth interview of 15 selected respondents. The research also revealed that Abang Yusuf Puteh succeeded in playing an important role in his effort to transform the culture of leadership towards a much better direction. Some of them were to propose motion in the State Legislative Assembly so society’s development given priority compared to job scope outside their jurisdiction. Besides, he succeeded in obtaining approval from the Speaker of the State Assembly to allow each member of the state assembly to bring two observers when the Sarawak State Legislative Assembly debate was taking place. Moreover, in the aspects coastal society in school, robustness of the education infrastructure, heightening the awareness on the importance of education among parents. His role in strengthening education also was seen through the changes in education system besides proliferation in the aspect of moral. In the aspect of economy, he had given agriculture aid to the residents, trained the residence to be independent and fought for development of the Malay coastal society. Hereafter, to strengthen religion among the Malay coastal society, Abang Yusuf Puteh succeeded in obtaining solid support to demolish customs and cultures that were diverse from the Islamic teaching in ‘Angkatan Nahdatul Islam Bersatu’ (BINA) muktamar. Other achievements were establishing the ‘Setia’ mini mosque and opening a free religious education classroom for the Malay coastal residents. He was generous and made his home as a place to educate Islamic religion. Finally, Abang Yusuf Puteh’s rebuke and effort succeeded in returning the prestige and standing of the Sarawak Malay society’s so they were not lagging from the current modernization.